A review on Activated Carbon Prepared from Agricultural Waste using Conventional and Microwave Activation - Taki, Estapraq Ameen; Salman, Sami D. (Al-Khwarizmi Engineering Journal, 2023)
In the recent years the research on the activated carbon preparation from agro-waste and byproducts have been increased due to their potency for agro-waste elimination. This paper presents a literature review on the synthesis of activated carbon from agro-waste using microwave irradiation method for heating. The applicable approach is highlighted, as well as the effects of activation conditions including carbonization temperature, retention period, and impregnation ratio. The review reveals that the agricultural wastes heated using a chemical process and microwave energy can produce activated carbon with a surface area that is significantly higher than that using the conventional heating method.